PENGARUH KEPUASAN PRODUK, KEPUASAN LAYANAN, DAN PENGALAMAN BERBELANJA TERHADAP LOYALITAS PELANGGAN MIE GACOAN KOTA SUNGAILIAT, KABUPATEN BANGKA - Abdillah Zahid At-Taqiy; Reski Mauliana; Lamia Eva Rini; Lusi Olis Vera; Ummu Artha Tsary Rumalessin (Jurnal Entrepreneur dan Manajemen Sains (JEMS), 2026)
This study analyzes the effect of product satisfaction, service satisfaction, and shopping experience on customer loyalty at Mie Gacoan Sungailiat. Using a quantitative approach, 50 respondents were surveyed and analyzed via multiple linear regression in SPSS. The results show that while simultaneously significant, partially only product satisfaction and shopping experience significantly affect loyalty, whereas service satisfaction does not. These variables explain 63.1% of loyalty variance. Despite sample limitations, this study contributes by suggesting management prioritize product quality and store atmosphere over service interactions to maintain loyalty. Kata Kunci: product satisfaction, service satisfaction, shopping experience, customer loyalty.